2019
DOI: 10.1002/ccr3.2382
|View full text |Cite
|
Sign up to set email alerts
|

A case of paediatric bladder bilharzioma in Johannesburg, South Africa

Abstract: On cystoscopy, a polypoidal tumor was observed and biopsied, and histology confirmed it to be an inflammatory mass with schistosoma eggs called a bilharzioma. We highlight this case to emphasize the silent destructive potential of schistosomiasis which the World Health Organization considers a Neglected Tropical Disease (NTD). A high degree of suspicion is often needed at the primary health care level to prevent morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…e mean age of our patients was 27 years which is in accordance to the higher prevalence of this infection in young adults [8] and children [5,10].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…e mean age of our patients was 27 years which is in accordance to the higher prevalence of this infection in young adults [8] and children [5,10].…”
Section: Discussionsupporting
confidence: 84%
“…He also observed that fibrocalcic and villous polyps were associated with lesions of chronic bilharzian cystitis in the majority of cases and active lesions in a minority of cases (8.8%). Pinto et al had also observed lesions of active bilharziasis associated with granulomatous polyps [ 5 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. haematobium lives in the pelvic venous plexus of the bladder of humans and eggs are sometimes shed in urine [9]. These eggs have a terminal spine that penetrates surfaces it attaches itself to and also causes haematuria when it travels down the wall of the urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
“…About 90 million people are infected worldwide. 6 The clinical manifestations depend on the inflammatory response to parasite infection. In particular, it can manifest in the bladder as painless dysuria, urinary incontinence, and urinary frequency or hematuria.…”
Section: Discussionmentioning
confidence: 99%